Good naked : reflections on how to write more, write better, and be happier - Cole, Joni B. (University Press of New England, 2017)
In Good Naked, acclaimed author Joni B. Cole shows readers how to make the writing process not only more productive, but less maddening, more inviting, and even joyful, at least a good part of the time. She explains how sharing early drafts is "good naked"--You're exposing your creative process in all its glory. Through a mix of engaging stories and practical wisdom, all delivered with sheer good humor, Cole addresses the most common challenges writers confront and offers disarmingly simple but effective solutions. She debunks popular misconceptions about how we are supposed to write and replaces them with strategies that actually work to get us started and stay motivated. (Searching for your muse? Try looking in the fridge.) With a do-this-not-that directness, she sets writers free from debilitating attitudes, counterproductive practices, and energy-draining habits that undermine confidence and creativity. Equipped with experience and a refreshing respect for anyone who wants to write, Cole also infuses every chapter with insights into craft and narrative technique--because the truly happy ending is not just that we write more, but that we write well. If you have ever experienced a sense of dread or intimidation at any stage of the creative process, or even if you simply want to write more, write better, and be happier, this intelligent, funny, and generous guide will not only inspire you to head over to your desk, but will also cheer you on once you're there.